2009
DOI: 10.1124/jpet.108.146878
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of the Blood-Brain Barrier to a Rhenacarborane

Abstract: The treatment of brain malignancies with boron neutron capture therapy depends on their ability to cross the blood-brain barrier (BBB). An especially promising class of boron-containing compounds is the rhenacarboranes that, if able to cross the BBB, could act as delivery vehicles as well as a source of boron. Here, we examined the ability of the 3-NO-3,3-2 -(2,2Ј-N 2 C 10 H 6 (Me){(CH 2 ) 7 131 I}-4,4Ј)-closo-3,1,2-ReC 2 B 9 H 11 (rhenacarborane) labeled with iodine-131 to be taken up into the bloodstream aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…One advantage of half‐sandwich metallacarboranes is the incorporation of biologically relevant ligands in the coordination sphere of the metals, as in the present study, where [3‐(2,2′‐bipyridine‐κ 2 N , N ′)‐3‐(CO) 2 ‐ closo ‐3,1,2‐MoC 2 B 9 H 11 ] ( i ) was equipped with a vector molecule which was inspired by the well‐known tamoxifen. Further examples were reported by Causey et al., Hawkins et al., Pruitt et al . and Louie et al .…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…One advantage of half‐sandwich metallacarboranes is the incorporation of biologically relevant ligands in the coordination sphere of the metals, as in the present study, where [3‐(2,2′‐bipyridine‐κ 2 N , N ′)‐3‐(CO) 2 ‐ closo ‐3,1,2‐MoC 2 B 9 H 11 ] ( i ) was equipped with a vector molecule which was inspired by the well‐known tamoxifen. Further examples were reported by Causey et al., Hawkins et al., Pruitt et al . and Louie et al .…”
Section: Introductionmentioning
confidence: 69%
“…[4] One advantage of half-sandwich metallacarboranes is the incorporation of biologically relevant ligands in the coordination sphere of the metals, as in the present study, where [3-(2,2'bipyridine-k 2 N,N')-3-(CO) 2 -closo-3,1,2-MoC 2 B 9 H 11 ] (i) was equipped with a vector molecule which was inspired by the well-known tamoxifen. Further examples were reported by Causey et al, [10] Hawkins et al, [11] Pruitt et al [12] and Louie et al [13] who used stable and hydrophobic rhenacarboranes including the [Re(L)(CO) 2 ] fragment (L = 2,2'-bipyridine derivative or [NO] + ) as imaging agents.…”
Section: Introductionmentioning
confidence: 99%
“…After 2 months of oral gavage (0.5 mg/kg), we found a significant decrease in Aβ plaque burden in several brain areas, such as the cortex, and the CA1, CA3, and DG regions of hippocampus ( Figure 3 ), suggesting that the TBSA crosses the blood brain barrier, permeates into the brain tissue, and inhibits amyloidogenic pathways, either by reducing Aβ production or preventing its aggregation. Although we did not measure the boron levels in the TBSA-treated mice brain tissue, previous studies have shown that boron compounds can cross the blood brain barrier and penetrate the brain tissue [ 32 ] and decrease inflammatory responses [ 33 ]. Combined with previous research showing efficacy of boron compounds in the brain [ 3 , 4 , 5 , 6 , 7 ], our findings of the efficacy of TBSA in the present study strongly suggest that TBSA is sufficiently permeable to brain tissue to reduce AD pathology.…”
Section: Discussionmentioning
confidence: 99%
“…A C C E P T E D ACCEPTED MANUSCRIPT 4 In preliminary studies with the 131 I-labeled prototypical rhenacarborane complex 3,3-κ 2 -(2,2'-N 2 C 10 H 6 (Me){(CH 2 ) 7 131 I}-4,4')-closo-3,1,2-ReC 2 B 9 H 11 ] (2), we have demonstrated the ability of a rhenacarborane to penetrate the BBB [9]. We determined rapid uptake and equilibrium phases with a steady state of ca.…”
Section: A N U S C R I P Tmentioning
confidence: 94%